The Development of an Android-Based E-Module In the History of Da’wah Coursein State Islamic Universities - Seprian Ilham; Ramalis Hakim; Novri Hardian (International Journal of Educational Dynamics, 2020)
In the course of the History of Da’wah at the Imam Bonjol State Islamic University of Padang, it is adequate for the student learning process.However,due to COVID-19, it requires an innovation that utilizes technology that must comply with health protocols, and must also be able to achieve maximum learning outcomes. This study was conducted in the midst of the COVID-19 pandemic as a learning technology innovation in dealing with the world disaster that have an impact in the field of education. This study aimed to determine the development and feasibility of the e-module of the History of Da’wah on the learning outcomes of the History of Da’wah course. This type of study was a Research and Development (Rand D) using the IDI (Instructional Development Institute) development model. The assessment of media experts, material experts, linguists, student and lecturer practicality were used as research data which were analysed by descriptive percentages.This studyproduced a product of the e-module of the History of Da’wah with the assessment of material experts of 79.17%, media experts of 80%, linguists of 78%, student responses of 85.42%, and teacher responses of 93.18%. Based on the results of this study, it can be concluded that the product of the e-module of the History of Da’wah is suitable for use in student learning for the History of Da’wah course at the Imam Bonjol State Islamic University of Padang.